Enteroinsular axis: physiology and pathophysiology : Metabolic and pleiotropic effects of incretins - Gonzalez, Claudio (2009)
A better understanding of GLP-1 and GIP biology, physiology and pathophysiology are currently within the focus of many labs across the world, since they are in the basement of the development of new therapies for treating type 2 Diabetes and obesity. Many of the main aspects of the incretins physiology are naturally complex, because a myriad of pleitropic actions, involving several biological systems, displaying marked interspecies and inter-individual variability. The search for new regulatory mechanisms involving the entero-insular axis is also extremely active, and novel promising compounds are currently being studied. Even when it results impossible to predict the long term success of the pharmacological intervention on these new targets, further advances in this area are granted.